Asuhan Kebidanan Continuity of Care (COC) pada Ny. V Umur 20 Tahun G2P1A0 dengan Ketidaknyamanan Melalui Penerapan Komplementer di Puskesmas Lerep - Neni Ratna Setiawati; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2025)
Continuity of care or continuity of midwifery care is an approach that is carried out continuously from pregnancy, childbirth, postpartum, to newborn care. This aims to improve the quality of maternal and infant health and ensure optimal monitoring. This care aims to provide an overview of continuity of care midwifery care for Mrs. R, 25 years old. The method in providing Continuity Of Care care uses a case study approach with direct observation and recording of care provided from the first trimester of pregnancy to the third trimester of pregnancy, childbirth, postpartum, infant care to family planning. Data were collected through interviews, observations, and documentation. The results of continuous midwifery care succeeded in increasing maternal compliance in undergoing prenatal care, minimizing complications during childbirth, and providing better knowledge about newborn care. The mother showed good health conditions during and after the delivery process, and the baby was born healthy. Conclusion: The continuity of care approach to Mrs. R showed positive results, providing a significant impact in improving maternal and infant health. Continuous midwifery care is highly recommended to be implemented in health facilities to ensure holistic monitoring of maternal and infant health. Abstrak Continuity of care atau kesinambungan asuhan kebidanan adalah pendekatan yang dilakukan secara terus menerus dari masa kehamilan, persalinan, nifas, hingga perawatan bayi baru lahir. Studi ini bertujuan memberikan asuhan kebidanan berkesinambungan (Continuity of Care) pada Ny. V usia 20 tahun untuk memastikan pemantauan kesehatan maternal dan neonatal yang optimal. Metode deskriptif dengan pendekatan studi kasus dilakukan di Puskesmas Larangan pada bulan Juni-Oktober tahun 2025. Data primer dikumpulkan melalui wawancara, observasi fisik, dan dokumentasi SOAP. Hasil asuhan menunjukkan kehamilan berjalan fisiologis, persalinan berlangsung spontan (Kala II selama 30 menit), bayi lahir bugar dengan BB 3000 gram, dan masa nifas tanpa komplikasi disertai keberhasilan pemberian ASI eksklusif. Pendekatan CoC pada Ny. V terbukti efektif dalam deteksi dini risiko dan meningkatkan kesiapan ibu dalam perawatan bayi serta pemilihan kontrasepsi.